Planktonic algae as bioindicators of water quality in Pagbanganan River, Baybay City, Leyte - Seriño, Eunice Kenee L.; Belonias, Beatriz S. (Annals of Tropical Research, 2020)
Biological monitoring is a valuable method used in conservation studies to protect and preserve the biological integrity of natural ecosystems. This study was conducted to assess the water quality of the Pagbanganan River using planktonic algae as bioindicators of organic pollution. Horizontal tows were made in three selected stations (upstream, midstream & downstream) using a Wisconsin plankton net with 80pm mesh size. Collected samples were preserved with Lugol’s solution and 70% ethyl alcohol. Identified phytoplankton genera were analyzed using Palmer’s Pollution Index. Out ofthe 20 pollution indicator genera identified by Palmer (1969), 10 were present in Pagbanganan River, namely; Ankistrodesmus, Closterium, Cyclotella, Gomphonema, Melosira, Navicula, Nitzschia, Oscillatoria,Stigeoclonium and Synedra. Four of these were among the most abundant algae in the river. Mean Palmer’s Pollution Index Scores indicate that there is “less” organic pollution existing in the river. Results imply that the river is still relatively safe for general household use, but effective conservation measures should be done to preserve the integrity ofthe river ecosystem.